2021
DOI: 10.1155/2021/8811898
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Cases of Acute Appendicitis

Abstract: Objectives. To investigate whether the incidence of acute appendicitis increases in summer and whether complicated cases present more in summer. Methods. A single-center cross-sectional, retrospective study on 697 cases of appendicitis admitted in the year 2018. Inclusion criteria: patients admitted with acute appendicitis who underwent appendectomy of all ages. Exclusion criteria: conservative management. Analysis was performed using Microsoft Excel. Pearson correlation coefficient was calculated to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
3
4
0
Order By: Relevance
“…The prevalence of cute appendicitis was moderately positive and negatively correlated with rainfall and sunlight hours. Our findings align with previous studies conducted on this issue in Nigeria (24), Cameroon(23),UK (28), Pakistan(30), India(7), Bahrain(10), Nepal(27), Irag(29), Iran(32). other studies reported higher prevalence of acute appendicitis during the Winter and Autumn season in Yemen (26), winter and autumn in Turkey (39).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of cute appendicitis was moderately positive and negatively correlated with rainfall and sunlight hours. Our findings align with previous studies conducted on this issue in Nigeria (24), Cameroon(23),UK (28), Pakistan(30), India(7), Bahrain(10), Nepal(27), Irag(29), Iran(32). other studies reported higher prevalence of acute appendicitis during the Winter and Autumn season in Yemen (26), winter and autumn in Turkey (39).…”
Section: Discussionsupporting
confidence: 92%
“…However, further research is needed on trends in appendicitis incidence in populations consuming traditional diets with different fiber content. The study found that the role of temperature and relative humidity in seasonal variation was weaker, similar to the research conducted in Bahrain (10).…”
Section: Discussionsupporting
confidence: 82%
“…Other research studies have reported similar findings. AlHarmi et al (2021) found that among 646 patients diagnosed with appendicitis, 500 (77.4%) were males [10]. Research studies that investigated the risk of appendicitis between males and females indicated that males are at a higher risk of developing acute appendicitis than females [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Rotavirus infection, the most prevalent cause of enterocolitis, has been shown to have no connection to the development of appendicitis [16]. Because of easy communication and a variety of lowfiber diets, older children are more likely to be detected with appendicitis [17], [18]. The inflammatory response is a well-coordinated mechanism that eliminates germs and dead tissue.…”
Section: Discussionmentioning
confidence: 99%